Sealworm Nematode Pseudoterranova decipiens (Krabbe, 1878) Gibson, 1983 (Nematoda: Rhabditida: Anisakidae) - Chad L. Cross; Peter DiGennaro (EDIS)
Contents: Introduction – Synonymy – Distribution – Description – Life Cycle and Biology – Hosts – Medical Importance – Economic Importance – Management – Selected References.